Cross-identification of stellar catalogs with multiple stars: Complexity and Resolution - Severín, Daniel Esteban (2018)
Fil: Fil: Severín, Daniel. Universidad Nacional de Rosario. FCEIA. CONICET. Rosario; Argentina